Transvaginal Ultrasound as an Indicator of Preterm Birth - Wibisono, Jacobus Jeno; Onasis, Serena; Nikendari, Sri Mulyani Rana; Andhika, Aryasena; Wibisono, Maria Georgina (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Preterm Birth is delivery that occurs when the mother's gestational age is 20-36 weeks starting from the first day of the last menstrual period with a fetal weight still below 2500 grams. In preterm birth there are regular uterine contractions that cause thinning or dilation of the cervix before 36 weeks of gestation is complete. Approximately 50% of sequelae that occur in children are due to preterm birth. It is known that cervical dilatation in pregnant women is associated with preterm birth, so there are several screening methods that are used to predict preterm birth, including cervical length examination. Transvaginal ultrasound examination is a safe method of examination to measure cervical length objectively. Cervical length less than or equal to 25 mm or cervical dilatation 70% to 100% are expected to have preterm birth.